Język, tekst, komunikacja : studia i szkice - Labocha, Janina (2021)
LANGUAGE, TEXT, COMMUNICATION: STUDIES AND OUTLINESThe book presents chosen articles of Prof. Janina Labocha, written in 1981–2019, and published earlier in scientific journals and collective volumes. It consists of three parts: „Syntax, linguistic pragmatics, text linguistics”, „Polish-Czech linguistic borderland” and „Varia”. The book contains 37 texts in total.